Penerapan Produksi Bersih Pada Industri Pembuatan Tempe, Di Desa Jubang, Kec. Bulakamba, Kab. Brebes, Jawa Tengah - Ameliya, Nely Kurotul (Jounal of Enviromental Science Sustainable, 2020)
The background: Tempe is a food that is already familiar to the people of Indonesia. Tempe is a traditional Indonesian food made by fermentation using Rhizopus sp. Tempe is made from soybeans with high protein 32 %. The purpose of this research is to examine the application of clean production in the tempe industry through mass balance, to analyze the feasibility of clean production alternatives technically and environmentally and to determine the application of clean production. The research method: consists of identification of the production process, analyzing the application of clean production and determining the strategy of clean production. The processing carried out in production is the process of selecting soybeans, washing I, boiling, soaking, washing II, milling, washing III, fermenting and packaging. The production scale in this case study is 15 kg per day to produce 16,800 kg. The results: of implementing clean production in the home industry of making tempe are good house keeping, recycle, reduce and reuse. Based on several eligibility criteria, alternative implementation of clean production for this industry in the form of equipment modification, machinery. The conclusion of this study is that the tempe industry does not yet recognize clean production. Benefits derived from implementing cleaner production in the form of savings in production costs and environmental cleanliness.